Product Schema Integration for Electronic Commerce: A synonym comparison approach - YAN, Guanghao (Institutional Knowledge at Singapore Management University, 2002)
In any electronic commerce system, the heterogeneity of product descriptions is a critical impediment to efficient business information exchange. In the ABECOS electronic commerce system, buyer agents, seller agents, and directory agents liaise with one another in e-commerce activities. Only when agents have a common ontology of product descriptions (also called product schemas) are they able to interact seamlessly in e-commerce activities. This gives rise to the product schema integration problem (PSI); the problem of integrating heterogeneous schemas of a certain product into one globally compatible schema. We adopt an integration approach based on product attribute synonyms. We give a formal definition of the problem and show that it is NP-complete. We contrast our approach of study to conventional schema integration in federated databases. We also propose a set of approximate algorithms for PSI and evaluate their performance